Large-scale disasters : prediction, control, and mitigation - Gad-el-Hak, Mohamed, 1945- (Cambridge University Press, 2008)
This volume presents an integrated review of the broad research field of large scale disasters. It establishes a common framework for predicting, controlling and managing both manmade and natural disasters. There is a particular focus on events caused by weather and climate change.